The Adventures of Baron Munchausen [videorecording (DVD)] - Gilliam, Terry; Gilliam, Terry; Neville, John, 1925-2011; Idle, Eric; Polley, Sarah; Reed, Oliver, 1938-1999; Thurman, Uma (Sony Pictures Home Entertainment, 2008)
The amazing journeys of Baron von Munchausen, who sets sail in a hot air balloon in search of his old comrades-at-arms with the object of saving a European city from the superior forces of a Turkish sultan.